Sufi mystery/ edited by Nathaniel P. Archer - "Shah, Idries" (New Delhi, 2007)
The Sufis is the best introduction ever written to the philosophical and mystical school traditionally associated with the Islamic world.Powerful, concise, and intensely thought-provoking, it sums up over a thousand years of Eastern thought into a single work, presenting timeless ideas in a fresh and contemporary style.
Keywords: Sufism